2021
DOI: 10.1111/bjet.13065
|View full text |Cite
|
Sign up to set email alerts
|

Never‐ending repetitiveness, sadness, loss, and “juggling with a blindfold on:” Lived experiences of Canadian college and university faculty members during the COVID‐19 pandemic

Abstract: We report on the lived experiences of faculty members during the early months of the COVID‐19 pandemic, exploring the broader experiences of faculty members as individuals living multifaceted lives whose homes became their offices, their students scattered geographically and their home lives upended. Using a phenomenological approach for data collection and analysis, we conducted 20 in‐depth interviews with faculty holding varied academic appointments at universities across Canada. Experiences during the early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 20 publications
3
63
0
Order By: Relevance
“…As the pandemic progressed, it became clear that there were additional considerations that affected online teaching success. Online courses still require faculty to provide learning material and communicate directly with students (Swan, 2019), and the change in communication format initially became a source of anxiety for many (Unger & Meiran, 2020; VanLeeuwen et al., 2021). Though many instructors were unprepared for the new teaching medium, many instructors and students alike later benefitted from the flexibility of material and classroom “space” that could be accessed anytime and from any place.…”
Section: Introductionmentioning
confidence: 99%
“…As the pandemic progressed, it became clear that there were additional considerations that affected online teaching success. Online courses still require faculty to provide learning material and communicate directly with students (Swan, 2019), and the change in communication format initially became a source of anxiety for many (Unger & Meiran, 2020; VanLeeuwen et al., 2021). Though many instructors were unprepared for the new teaching medium, many instructors and students alike later benefitted from the flexibility of material and classroom “space” that could be accessed anytime and from any place.…”
Section: Introductionmentioning
confidence: 99%
“…However, 48% encountered Internet-related problems, 44% reported difficulty in adapting the curriculum to distance education and 65% had issues providing exams to students ( Kalanlar, 2022 ). In reaction to the COVID-19 measures implemented, nursing staff members in Canada were required to make the necessary preparation for remote learning by working longer hours to transition existing curriculum to suit remote teaching ( VanLeeuwen et al, 2021 ). The pandemic might have also affected their research projects.…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic might have also affected their research projects. A few studies from Canada and Kosovo found that faculty members often felt overwhelmed by work ( VanLeeuwen et al, 2021 ) and faced stress and uncertainty due to the lack of prior experience in conducting E-learning ( Duraku and Hoxha, 2020 ). The stress and anxiety arising from the changes caused by the COVID-19 pandemic might affect their mental health.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon can arise from non-transparent communication on both sides: Students may not be aware of the teachers' efforts in online teaching, and teachers may have lost sense of their students' well-being. Teachers experienced remote education in the pandemic negatively as well (Moorhouse & Kohnke, 2021;VanLeeuwen et al, 2021), and communicating such struggles to students may create a sense of common humanity. The feeling of being in it together and acknowledging one another's problems could then contribute to a greater feeling of relatedness.…”
Section: Implications and Further Researchmentioning
confidence: 99%